Recent developments in restorative justice for young people in England and Wales - Crawford, Adam (The British journal of criminology, 2002)
This article examines some recent attempts to introduce elements of restorative justice into the youth justice system. We focus on the introduction of referral orders and youth offender panels and, in particular, consider the issues of community participation and representation. In examining the early experiences of these new ways of working we highlight a series of questions that arise out of the tension between the participatory character of restorative justice and the managerialist nature of much contemporary youth justice in England and Wales